New strategy to improve quality control of Montenegro skin test at the production level - Deborah Carbonera Guedes; João Carlos Minozzo; Aline Kuhn Sbruzzi Pasquali; Craig Faulds; Carlos Ricardo Soccol; Vanete Thomaz-Soccol (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: The production of the Montenegro antigen for skin test poses difficulties regarding quality control. Here, we propose that certain animal models reproducing a similar immune response to humans may be used in the quality control of Montenegro antigen production. METHODS: Fifteen Cavia porcellus (guinea pigs) were immunized with Leishmania amazonensis or Leishmania braziliensis , and, after 30 days, they were skin tested with standard Montenegro antigen. To validate C. porcellus as an animal model for skin tests, eighteen Mesocricetus auratus (hamsters) were infected with L. amazonensis or L. braziliensis , and, after 45 days, they were skin tested with standard Montenegro antigen. RESULTS: Cavia porcellus immunized with L. amazonensis or L. braziliensis , and hamsters infected with the same species presented induration reactions when skin tested with standard Montenegro antigen 48-72h after the test. CONCLUSIONS: The comparison between immunization methods and immune response from the two animal species validated C. porcellus as a good model for Montenegro skin test, and the model showed strong potential as an in vivo model in the quality control of the production of Montenegro antigen.